Evaluation of the Implementation of Religious Moderation with the CIPP Model: Moderate Character of High School Students - Alias, Hamzah; Mania, Sitti; Rasyid, Muhammad Nur Akbar (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Religious moderation is a moderate view on religion. The government has made religious moderation a national policy to organize and harmonize Indonesia's heterogeneous religious life. Educational institutions are key to strengthening this program. Evaluation is necessary to make educational religious moderation initiatives more quantitative and targeted. This study aims to evaluate the implementation of the religious moderation program at the public high school. This study uses a qualitative approach with the CIPP evaluation model. This research was conducted at the Public High School 7 Wajo. Data collection was carried out using interview, observation, and documentation techniques. Data analysis techniques used the interactive model from Miles and Huberman. The techniques used for checking data validity included triangulation methods. The findings indicate that Public High School 7 Wajo is effectively implementing religious moderation in a comprehensive way, as seen in their Education Unit Curriculum document, regular classes, extracurricular activities, daily practices, school policies, and interfaith student groups. The CIPP evaluation shows that the program is going well and should be continued with improvements. The evaluation results indicate that the program has run well: a clear legal basis, program objectives that meet program recipients' needs, principal support, cooperation with the Wajo Regency Interfaith Harmony Forum, utilizing opportunities to become advantages, ignoring obstacles so that program implementation runs continuously and sustainably, and successfully forming moderate student character.